2021
DOI: 10.1002/ente.202100628
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Graphite Electrode for Lithium‐Ion Battery with High Areal Capacity

Abstract: Combined with the traditional preparation method of graphite anode slurry for lithium battery and the manufacturing technology of pneumatic jet, the organic solvent‐based anode slurry is selected to explore the viscosity curve under different solid–liquid ratios. It is judged that the anode slurry is a non‐Newtonian fluid. It has printability and meets the requirements of direct writing molding technology. The slurry with a solid volume fraction of 50% is selected as the printing material, the graphite anode s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Regarding the electrodes, on the one hand Zhang et al reported a method to obtain LDM printed ones with commercial graphite slurry 81 . They obtained remarkable capacity values in comparison with traditional electrodes used in LIB.…”
Section: Polymer and Polymer Composites For Batteries Obtaining And T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the electrodes, on the one hand Zhang et al reported a method to obtain LDM printed ones with commercial graphite slurry 81 . They obtained remarkable capacity values in comparison with traditional electrodes used in LIB.…”
Section: Polymer and Polymer Composites For Batteries Obtaining And T...mentioning
confidence: 99%
“…A huge amount of the 3D-printed LIB electrolytes 91,92 and electrodes 81 were obtained by LDM process, also known as direct ink writing. 93,94 The LDM method involves a syringe which prints the fed ink by a pneumatic system (Figure 5A).…”
Section: Liquid Deposition Modelingmentioning
confidence: 99%
“…For cathode materials, some widely used cathode materials have been successfully applied for 3D printed lithium batteries including lithium cobalt oxides (LiCoO 2 ) (Kohlmeyer et al, 2016), lithium manganese oxides (LiMn 2 O 4 ) (Li et al, 2017), lithium transition-metal phosphates (LiMn 1-x Fe x PO 4 ) (Hu et al, 2016), etc., as well as other materials with higher capacities involving carbon materials (graphite and graphene) (Mensing et al, 2020;Zhang et al, 2021), silicon materials (Beydaghi et al, 2021), and quantum dots (Zhang et al, 2018b). For anode materials, some conductive frameworks such as carbon and 2D MXenes (Ti 3 C 2 T x ) can severe as current collectors for hosting Li (Wei et al, 2021).…”
Section: Materials Selectionmentioning
confidence: 99%
“…The traditional coating method is to disperse the prepared AlPO 4 particles in water to form a dispersion and then add the cathode material particles to the above dispersion so that the AlPO 4 particles are adsorbed on the surface of the LiNi 0.5 Mn 1.5 O 4 particles through adsorptive action, and heat treatment is carried out after evaporation of water to form a cathode active material with AlPO 4 particles on the surface. However, because AlPO 4 is insoluble in water, AlPO 4 particles are easy to agglomerate in water and difficult to disperse. Moreover, when a large number of cathode material particles are added to the AlPO 4 dispersion, local cathode material particles will adsorb a large amount of AlPO 4 , while some cathode material particles may not adsorb enough AlPO 4 . , Therefore, the method is difficult to form a uniform AlPO 4 coating on the surface of the electrode, so it is difficult to achieve the purpose of better improving material properties. Considering the above-mentioned facts, the LiNi 0.5 Mn 1.5 O 4 /AlPO 4 composites were synthesized by an in situ coating method in this paper.…”
Section: Introductionmentioning
confidence: 99%